2021
DOI: 10.1001/jamapsychiatry.2020.4768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incentives for Alcohol Abstinence in Partnership With 3 American Indian and Alaska Native Communities

Abstract: and Alaska Native communities are disproportionately affected by problems with alcohol use and seek culturally appropriate and effective interventions for individuals with alcohol use disorders.OBJECTIVE To determine whether a culturally tailored contingency management intervention, in which incentives were offered for biologically verified alcohol abstinence, resulted in increased abstinence among American Indian and Alaska Native adults. This study hypothesized that adults assigned to receive a contingency m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
(61 reference statements)
1
30
0
Order By: Relevance
“…Another notable strength of this research is the community-based participatory research approach taken. From using focus groups to constructing a community advisory board, the study design and implementation of the culturally adapted intervention were completed with community input and tribal oversight.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Another notable strength of this research is the community-based participatory research approach taken. From using focus groups to constructing a community advisory board, the study design and implementation of the culturally adapted intervention were completed with community input and tribal oversight.…”
mentioning
confidence: 98%
“…In this issue of JAMA Psychiatry , McDonell et al reported the results of a 12-week multisite randomized clinical trial of CM for the treatment of AUD among American Indian and Alaska Native adults in which rewards were provided for abstinence verified by ethyl glucuronide (EtG), a biomarker of recent alcohol use. Four hundred individuals were enrolled in a 4-week observation and qualification period in which they could receive treatment as usual and incentives for providing urine samples twice weekly for measurement of EtG.…”
mentioning
confidence: 99%
See 3 more Smart Citations